Optimization of antiscorpion venom production - Ozkan,O. (2006)
The present study was carried out to produce highly efficient antivenom from a small number of telsons in a short time. Venom solution was prepared through maceration of telsons from Androctonus crassicauda (Olivier, 1807) collected in the Southeastern Anatolia Region, Turkey. Lethal dose 50% (LD50) of the venom solution injected into mice was 1 ml/kg (95% confidence interval; 0.8-1.3), according to probit analysis. Different adjuvants (Freund's Complete Adjuvant, Freund's Incomplete Adjuvant, and 0.4% aluminium phosphate), at increasing doses and combined with venom, were subcutaneously injected into horses on days 0, 14, 21, 28, 35, and 42 of the experiment. Antivenom was collected from the immunized horses on days 45, 48, and 51 using the pepsin digestive method. The antivenom effective dose 50% (ED50) in mice was 0.5 ml (95% confidence interval; 0.40-0.58), according to probit analysis. It was concluded that 0.5 ml antivenom neutralized a venom dose 35-fold higher than the venom LD50. Thus, highly potent antivenom could be produced from about 238 telsons in 51 days.